Abracadabra 3.0: report on effectiveness of eposter presentation programme / Aileen Farida MohdAdam ... [et al.] - MohdAdam, Aileen Farida; Amin, Noraziah; Tazijan, Farina Nozakiah; Mohd Mohzan, Maizatul Akmal; Jamil, Marni; Abdul Halim, Muhammad Aiman; Musa, Muriatul Khusmah; Affendy, Noor Azli; Abdul Halil, Norhafizah; Hassan, Norhaslinda (Academy of Language Studies, 2022)
The Abracadabra 3.0 program is a poster presentation program that aims to increase self-confidence and English language ability, especially for pre-diploma students. This program is an annual program organised by Academy of Language Studies, UiTM Penang Branch to strengthen pre-diploma students’ language skills. This program is important to uncover students’ English language skills, improve knowledge transfer skills as well as to apply good values in preparing and presenting their respective group e-posters. In addition to language skills, soft skills are also very important to form pre-diploma students who are more competitive and able to continue their studies to a higher level. This semester’s 'Abracadabra 3.0: Pre-Higher Education E-Poster Competition' comes with the theme ' Traverse Malaysia 2022 ' on which students are free to choose to present on any topic related to Malaysia. The students were asked about their experience in completing the poster presentation task in terms of their skills in using visual aids, finding content for their poster, speaking English, delivering their speeches, working as a team and their overall feedback about the assignment